2022
DOI: 10.1155/2022/2286713
|View full text |Cite|
|
Sign up to set email alerts
|

Impact of BN and WC Particulate Reinforcements on Mechanical Properties and Damage Development of Al-2048 Metal Matrix Composites

Abstract: The primary goal of this work is to evaluate how BN and WC particles affect the mechanical properties and damage development behaviours of aluminum alloy-2048. Heat treatments for composites are also being investigated to improve mechanical properties. Tensile experiments reveal that BN particle reinforcement outperforms WC reinforcement in strength and flexibility for composites. T4 treatment, rather than traditional peak-aging treatment, is recommended for the composites (T6). The particle size distribution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(4 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…e capacity to manufacture the fiber to final CMC engine components for a broad range of modular components will be enabled by GE Aviation's quick and flexible vertical distribution chain. Various polymer and metal matrix composites also used in other applications [34][35][36][37][38].…”
Section: Ceramic Matrix Composites Taking Flight At Ge Aviationmentioning
confidence: 99%
“…e capacity to manufacture the fiber to final CMC engine components for a broad range of modular components will be enabled by GE Aviation's quick and flexible vertical distribution chain. Various polymer and metal matrix composites also used in other applications [34][35][36][37][38].…”
Section: Ceramic Matrix Composites Taking Flight At Ge Aviationmentioning
confidence: 99%
“…AA7075 materials have wide usage in many fields, such as gears and shafts for aerospace, bike frames, meter shafts, sprockets for terrain vehicle, worm gears and military spare parts, due to their weight-to-strength ratio, fatigue resistance and natural aging behaviours. Sivakumar et al [17] evaluated the properties of Al2048 composites reinforced with BN and tungsten carbide (WC) particles, and concluded that more strength and flexibility were obtained by adding BN particles. Gopinath et al [18] studied the properties of Al6061 composites with BN, Al 2 O 3 and Gr particles, as reinforcements.…”
Section: Introductionmentioning
confidence: 99%
“…In vehicles and trucks, locomotives, and general aviation, AZ31 magnesium alloys have the potential to replace several standard structural materials as lightweight alloys [1][2][3]. In recent years, eforts have been undertaken to further enhance these alloys' characteristics by using reinforcements such as Si 3 N 4 [4], SiC [5], BN-WC [6], Gr-WC [7], TiC-TiB 2 [8], and titanium [9]. Due to modifcations in the mechanism of solidifcation for nanosized reinforcements, composites exhibit phenomenal results in terms of strength when nanosized particles are added to the matrix of magnesium.…”
Section: Introductionmentioning
confidence: 99%